ANALISIS PENYERAPAN DANA ALOKASI KHUSUS DI KOTA PAYAKUMBUH TAHUN 2021 - 2025 - Nurma Yanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The Special Allocation Fund is one of the intergovernmental fiscal transfer instruments aimed at supporting the financing of national priority programs and activities as well as improving the quality of public services at the regional level. The success of Special Allocation Fund management is determined not only by the size of the budget allocation but also by the level of budget absorption and the effectiveness of its implementation. This study aims to analyze the level of Special Allocation Fund absorption in Payakumbuh City during the 2021–2025 period, compare the absorption characteristics between Physical Special Allocation Funds and Non-Physical Special Allocation Funds, and identify the factors influencing fund absorption. This study employs a descriptive approach using a quantitative-descriptive method. The data used are secondary data obtained from the Regional Revenue and Expenditure Budget, Budget Realization Reports, and Special Allocation Fund-related documents sourced from the Regional Financial Agency of Payakumbuh City. The analytical techniques applied include the calculation of budget absorption ratios, trend analysis, and comparative analysis between Physical and Non-Physical Special Allocation Funds. The results indicate that the level of Special Allocation Fund absorption in Payakumbuh City generally exceeded 90 percent throughout the observation period, although fluctuations and a decline occurred in 2024. Non-Physical Special Allocation Funds exhibit a relatively more stable absorption level due to their operational and routine nature, whereas Physical Special Allocation Funds encounter constraints during technical planning, procurement of goods and services, and the implementation of activities. The main factors affecting fund absorption include the quality of budget planning, human resource capacity, accuracy of administration and reporting, as well as central government policies and regulations. This study concludes that the management of the Special Allocation Fund in Payakumbuh City has been relatively effective and has contributed to the achievement of regional development objectives.Keywords: Special Allocation Fund, Budget Absorption, Physical Special Allocation Fund, Non-Physical Special Allocation Fund, Regional Finance